Conférences sans conférer ? Les conférences de l’Académie royale de peinture et de sculpture, 1648-1699 - Olivier Bonfait (Les Dossiers du GRIHL)
Based on the Procès-verbaux de l’Académie royale de peinture et de sculpture and the recent edition of the Conferences held in this institution by Jacqueline Lichtenstein and Christian Michel, this article examines the practices of the conferences between 1667 and 1699 and questions their status as a collective work. It insists on the tensions between this group work, from the writing of the lecture to its publication (printed or in the form of an official re-reading) and the weight of authorial strategies, in a logic of service or of auctorial appropriation, or of the expectations and presence of the monarchic power. The conclusion, through a parallel with the Royal Academy of Architecture, highlights the ambiguity of the place given to the writing among painters in the process of professionalization (or because of the very nature of their art), but shows the agreement on the formation of a lexicon, elaborated within but also outside the academic place.